Reference Based Genomic Data Compression Using R Programming - Rani, M. Mary Shanthi; Bose, S. Jegatheesh Chandra (International Journal of Computer Sciences and Engineering, 2025)
Genomics has become a hot research area in medical field for diagnosis of monogenetic disorder identification, pharmaco genetics, targeted therapy, genome editing and personalized medicine. Each human genome consists of 3 billion pairs which are to be effectively stored and transmitted for analysis. This process necessitates the development of novel genomic data compression algorithms. In this paper a referential based method for compressing genomes has been proposed. The input and reference genomes are compared for dissimilarities and further entropy coded to achieve high compression ratio